Co-crystal polymorphic control by nanodroplet and electrical confinement. Issue 18 (26th April 2019) - Padrela, L. M.; Castro-Dominguez, B.; Ziaee, A.; Long, B.; Ryan, K. M.; Walker, G.; O'Reilly, E. J.
Abstract : The polymorphic control of the co-crystal carbamazepine–saccharin (CBZ–SAC) metastable form II was achieved by nano-droplet confinement in tandem with droplet surface charging induced by electrospraying the precursor solution. Abstract : The polymorphic control of the co-crystal carbamazepine–saccharin (CBZ–SAC) metastable form II was achieved by nano-droplet confinement in tandem with droplet surface charging induced by electrospraying the precursor solution. Polymorphic exclusivity is independent of solvent selection. CBZ–SAC co-crystals obtained by electrospraying are compared with supercritical CO2 nano spray-drying, conventional spray-drying and solvent evaporation methods.